Transformasi Digital dan Literasi Teknologi Terhadap Profesionalisme Guru - Jannah, Raihanil; R, Rosdiana (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the relationship between digital transformation and technology literacy in strengthening teacher professionalism in the digital era. Teacher professionalism requires an integration of pedagogical, professional, social, and personal competencies with digital fluency. The research applied a qualitative approach using library research, limited interviews, and observations of teaching practices in several primary and secondary schools. The findings indicate that teachers with high technological literacy are more capable of designing interactive and adaptive learning as well as keeping up with educational technology trends. Digital transformation also facilitates broader professional collaboration and development through online platforms and digital learning communities. This study concludes that technology literacy is a vital foundation for supporting digital transformation and serves as a key indicator of sustainable teacher professionalism